Professor Nikolai Ilyich Blinov (1899–1971) (on the 125th anniversary of his birth) - N. I. Glushkov; M. V. Melnikov; G. M. Gorbunov; M. A. Ivanov (Вестник хирургии имени И.И. Грекова)
2024 marks the 125th anniversary of the birth of the outstanding surgeon, scientist, teacher and public figure, Doctor of Medical Sciences, Professor Nikolai Ilyich Blinov. N. I. Blinov was born on February 18, 1899 in Uglich, Yaroslavl province. In 1924, he completed his studies at the Petrograd State Institute of Medical Knowledge (GIMZ) and was left as a resident at the Department of General Surgery. From 1927 to 1931, N. I. Blinov worked as a surgical resident at the Institute of Surgical Tuberculosis. In 1932, he was appointed the head of the serological laboratory at the Research Institute of Blood Transfusion. According to the totality of scientific works, in 1935, N. I. Blinov was awarded the degree of candidate of medical sciences, and a year later, he defended his doctoral dissertation on the topic “The doctrine of blood groups and its significance in the clinic”. In 1939, he was elected the associate professor of the Surgical clinic No. 2 of the Leningrad State Institute for Advanced Medical Training. During the Great Patriotic War, he was the chief surgeon of several hospitals in besieged Leningrad; he continued to work in the State Institute for Advanced Medical Training for the training of medical personnel. In 1951, he was elected the professor of the surgical clinic No. 2 of the Leningrad State Institute for Advanced Medical Training, and since 1952 – Head of the Department of General Surgery of the Leningrad State Institute for Advanced Medical Training and headed it until 1968. In the period from 1954 to 1959, he served as director of the State Institute for Advanced Medical Training. He is the author of more than 200 scientific papers; 2 doctoral and 20 PhD theses have been defended under his supervision. N.I. Blinov paid great attention to public activities, was elected the member of the Leningrad City Council of Workers’ Deputies, the deputy of the Smolninsky district Council of Workers’ Deputies. He was awarded orders and medals of the USSR, Honored Scientist of the RSFSR (1967). He retired in September 1968. He died on April 15, 1971. He was buried at the Bolsheokhtinsky cemetery in St. Petersburg.